Indicators of carbohydrate and fat metabolism in patients with various degrees of fatty liver dystrophy - V.B. Yagmur; R.M. Kislova; I.A. Klenina; O.M. Tatarchuk; S.L. Melanich (Gastroenterologìa, 2022)
Background. Non-alcoholic fatty liver disease (NAFLD) ranks first among chronic liver diseases and covers almost a quarter of the population. Enough data have been accumulated on the mutual influence of metabolic changes and steatosis of the liver of varying degrees on the existence and progression of each other. The coexistence of non-alcoholic steatohepatitis (NASH) with various comorbidal conditions has already been recorded in many studies, a direct relationship has been determined between the presence of fatty degeneration and various components of the metabolic syndrome — arterial hypertension, type 2 diabetes, obesity and dyslipidemia. The purpose was to determine the relationship between carbohydrate and fat metabolism in patients with NAFLD depending on the degree of fat accumulation in the liver. Materials and methods. Data were obtained from 72 patients with NAFLD, who were divided into two groups according to the degree of steatosis. The I group included 46 patients with moderate steatosis (the proportion of hepatocytes containing fatty is 33–66 %). The indicator of the controlled parameter of ultrasonic attenuation (CAP) ranged from 232 to 256 dB/m. The II group consisted of 26 patients with severe steatosis (the proportion of hepatocytes containing fatty inclusions more than 66 %), with CAP more than 256 dB/m. The trophological status, the parameters of carbohydrate and fat metabolism were determined. A statistical analysis of the data was carried out — the mean values in the groups were compared and the contribution of variables to the value of CAP was estimated using the method of multiple regression analysis. Results. The level of insulin and HOMA-IR in patients with severe fatty degeneration of the liver was (22.7 ± 9.7) and (5.4 ± 2.7) μU/ml, respectively. These indicators were higher than the corresponding indicators of group I (p < 0.05), (17.1 ± 10.3) and (4.01 ± 2.9) μU/ml for insulin and HOMA-IR, respectively. Glucose, lipid spectrum did not differ significantly between the groups, except for the fraction of very-low density lipoproteins (VLDL), which were significantly higher in patients with a higher degree of fatty degeneration and amounted to 3.4 (2.3–4.1) and 3.0 (2.4–3.8) mmol/L in groups II and I, respectively. Multiple regression analysis was performed to determine the contribution of fat and carbohydrate metabolism to CAP values. As a result of step-by-step analysis, two indicators remained in the model, namely the HOMA index (regression coefficient β 5.285, p = 0.04) and BMI (regression coefficient β 4.666, p = 0.001). It was determined that changes in BMI and HOMA are responsible for 31 % of changes in the value of CAP. Conclusions. Insulin values, HOMA index, BMI and VLDL are higher in patients with severe steatosis. According to the results of multiple regression analysis, a significant contribution of HOMA and BMI values to the CAP was revealed.